Multicultural Education Approach - Wirdatul Hasanah; Mohammad Futuh Muafi; Siti Muthiatun Najiyah; Siti Aminah; Diah Ainun Khafidloh; Muhammad Hori (Classroom: Journal of Islamic Education, 2026)
This study aims to analyze multicultural education approaches in the development of Islamic education systems. Multicultural education is an important strategy in building tolerance, social justice, and respect for diversity. The research method used is library research with a descriptive qualitative approach. The findings show that the implementation of multicultural education can be carried out through curriculum integration, planned school programs, and the active role of teachers. This approach is relevant in shaping inclusive, democratic, and tolerant students.